Laboratory investigation of hydraulic characteristics of fly ash as a fill material from the aspects of pollutant transport - Stanić, Filip; Jaćimović, Nenad; Ranđelović, Anja; Despotović, Jovan (Water science and technology, 2017)
Depending on the usage of fly ash, it is necessary to determine its environmental parameters, such as the potential for pollutant transport/leaching after its built-in. This study presents a methodology for determination of transport parameters (filtration coefficient, effective porosity, longitudinal dispersivity, and the mean residence time) from experimental data collected from column experiments with a conservative tracer on different mixtures of fly ash with stabilizers (4.8% lime and 5% cement). The transport parameters are determined using (1) numerical model results and (2) an adapted analytical solution results against measured outflow tracer concentrations. The study shows that the addition of stabilizers decreases the filtration coefficient by an order of magnitude and the effective porosity by half. The longitudinal dispersivity is not influenced by the addition of lime to the mixture, and is increased by 40% by the addition of cement. The pollutant contact time with fly ash increases by six or nine times with the addition of lime and cement, respectively. The adaptation of the analytical solution agrees well with both the numerical solution and the experimental results, and it is anticipated to be of high value for determination of transport parameters for practitioners not familiar with numerical methods.